Employment protection legislation and entrepreneurial activity. (September 2019) - Liebregts, Werner; Stam, Erik
Labour market institutions enable and constrain individual behaviour on the labour market and beyond. We investigate two main elements of national employment protection legislation and their effects upon entrepreneurial activity. We use multilevel analyses to estimate the separate impact of redundancy payments and the notice period for employers on independent entrepreneurship (self-employment) and entrepreneurial employee activity. Redundancy payments and notice period reflect labour market friction, opportunity cost, search time and liquidity constraint mechanisms contained in employment protection legislation. Country-level legislation on the notice period for employers is found to be positively related to an individual's involvement in entrepreneurial employee activity, yet negatively related to self-employment. We do not find consistent effects of redundancy pay legislation on entrepreneurial activity.